Follow-up of kidney donors at a single center in South Africa - Naicker, S; Azor, M; Sukool, A; Holmes, I; Muranda, A; Haffejee, AA (African Journal of Nephrology, 2016)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background:There is a worldwide shortage of organ donors. Inour province, KwaZulu / Natal, this problem is morepronounced as the rate of cadaveric donation is verylow. Thus both patients and nephrology staff areunder pressure to seek living donors. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Methods and results:We studied 135 living kidney donors in ten yearsperiod: 85 females and 50 males; 78 (57.8%) were ofIndian origin, 33 (24.4%) Black, 15 (11.1%) Whiteand 9 (6.7%) of mixed race groups. The majority ofdonors (57%) were siblings, while 14.8% wereparents, 6.7% children, 17.8% spouses and 3.7%were cousins. The mean age of donors was 34.2 years(range 21-56 years). Donors were hospitalised for amean peroid of 6.1 days (range 3-15). Post-operativecomplications were left lobe atelectasis and chestinfection in 11.1 %, other infections in 5.2%,pneumothorax in 2.2%, ileus in two cases, depressionin one and prolonged pain at the site of surgery in11.1%. Proteinuria was noted in three cases (0.26gm/d and 0.66 gm/d in two donors at 2 years and 0.27gm/d in the third case at 10 years).Blood pressure levels were virtually unchanged frompre-nephrectomy data. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion:This study confirms that unilateral nephrectomy innormal individuals is associated with few major adverse effects and living donors in renal transplantation is a viable option.